Pendampingan Akuntansi Dalam Menentukan Harga dan Pengelolaan Persediaan Untuk Memajukan Usaha Masyarakat Desa Bangbang, Bangli - Desak Rurik Pradnya Paramitha Nida; I Gusti Agung Prama Yoga; I Nyoman Angga Prabawa (Universitas Warmadewa, 2024)
Financial statements play an important role in providing information for making business decisions or policies. Financial statements are the end result of the accounting process. However, there are still many stigmas in society that consider accounting to be difficult. In fact, if done consistently and orderly, the information obtained will greatly impact the sustainability of the business both as a source of information and a control tool. The most basic thing, in basic accounting that needs to be understood is the process of how financial statements are made. Starting from collecting transaction evidence, grouping, recording, analyzing and presenting accounting information. The first stage is collecting evidence. This initial stage is still widely ignored in recording. Even though transaction evidence is needed to prove the validity of transaction occurrences and measurements in transaction recognition. In collaboration with the Bangbang Village BUPDA, the service team conducted assistance involving the Tembuku Bangbang Bali Village community, namely traders, BUPDA (Baga Utsaha Padruwen Desa Adat) administrators and local LPD (Village Credit Institution) administrators in early June 2024 to get assistance and training on the role of accounting in advancing business, basic accounting, inventory methods, how to make transaction evidence by utilizing technology. The methods used were socialization and discussion groups. The obstacle so far that has been felt is the difficulty of compiling reports due to forgetting or not taking notes. Not everything is